HADITH UNDERSTANDING RECONSTRUCTION â€œWOMENâ€: DELIVERING THE ISLAMIC EDUCATION SYSTEM OF EGALITARIAN - M.Pd.I, Muri’ah; M.Pd.I, Munawir (Journal of Islamic Educational Research, 2017)
Lack of understanding about normative –nash- of hadith shows the wrong opinion about woman. This understanding is very insist to be reconstructed, it can find the real, normative, and universe of Islamic massages. The series, it will implicate relation of man and woman in many aspects, especially system of Islamic education. So, this writing tries to do reconstruction about understanding of refraction gender in understanding hadith about woman. This writing offers Islamic education which means educational systems is a system or material of educational. This study focuses empowerment of human (insha’ al-shay’ ila kamali-hi halan fa-halan) it based al-Qur’an and hadith in specific context. It means, this study is not only about normative aspect of Islamic theory, but also applied in many lessons, culture institution and the effect to empowerment of human, especially developing of intellect potential and intellectuals of human.